2018
DOI: 10.1080/13510347.2018.1542430
|View full text |Cite
|
Sign up to set email alerts
|

A tale of culture-bound regime evolution: the centennial democratic trend and its recent reversal

Abstract: with almost ten staff, and a project team across the world with four Principal Investigators, fifteen Project Managers (PMs), 30+ Regional Managers, 170 Country Coordinators, Research Assistants, and 2,500 Country Experts, the V-Dem project is one of the largest ever social science research-oriented data collection programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Source: Brunkert et al (2018, p. 6) democracy. Similarly, while acknowledging that there have been reversals in the trends of democratization, Brunkert et al (2018) emphasize that they have been only temporary. Like Inglehart, they provide reasons for optimism by pointing out that democracy's cultural seeds-emancipative values-have been rising over the generations and are doing so in most parts of the world, including such seeming strongholds of authoritarianism as China, Russia, Singapore, and Turkey.…”
Section: The Bird's-eye Perspective: the Centennial Trendsmentioning
confidence: 99%
See 3 more Smart Citations
“…Source: Brunkert et al (2018, p. 6) democracy. Similarly, while acknowledging that there have been reversals in the trends of democratization, Brunkert et al (2018) emphasize that they have been only temporary. Like Inglehart, they provide reasons for optimism by pointing out that democracy's cultural seeds-emancipative values-have been rising over the generations and are doing so in most parts of the world, including such seeming strongholds of authoritarianism as China, Russia, Singapore, and Turkey.…”
Section: The Bird's-eye Perspective: the Centennial Trendsmentioning
confidence: 99%
“…A recent survey of the state of democracy across the globe (Van Beek et al 2018) could not find any signs of democratic backsliding for the established democracies of the West, even if there were various problems in other parts of the world. Based on Varieties of Democracy (V-Dem) data, the best data currently available, Brunkert et al (2018) present the centennial democratic trends for democracy overall as well as for its participatory, liberal, and electoral components, which all have been rising in the long run (see Fig. 1).…”
Section: The Bird's-eye Perspective: the Centennial Trendsmentioning
confidence: 99%
See 2 more Smart Citations
“…Along similar lines, behavioral scientists such as Alexander and Welzel (2017), Inglehart (2016), and Norris and Inglehart (2019) claim that the level of democratic support is astonishingly high among all age cohorts in democratic societies. In a comparative and longitudinal analysis covering 116 years, Brunkert et al (2019) found that public support for democracy is closely associated with emancipative values. The authors show that the increasing class polarization and marginalization of lower classes are the real source of the current decreasing dissatisfaction with political institutions and their decision making.…”
Section: Challenges To Democracymentioning
confidence: 99%